[OP.4B.08] PROGNOSTIC RELEVANCE OF ELECTROCARDIOGRAPHIC TP-TE INTERVAL IN THE GENERAL AND IN THE HYPERTENSIVE POPULATION: DATA FROM THE PAMELA STUDY. (September 2016) - Bombelli, M.; Seravalle, G.; Maloberti, A.; Macchiarulo, M.; Boggioni, I.; Dell'Oro, R.; Cuspidi, C.; Mancia, G.; Grassi, G.
Abstract : Objective: Electrocardiographic (EKG) Tpeak-Tend (Tp-Te) interval, an index of transmural dispersion of myocardial repolarization, is gaining interest as possible cardiovascular (CV) prognostic variable. Evidence that this is the case in the general population is scanty, however. Design and method: This was tested in the Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) population. EKG, echocardiographic, office, home and ambulatory (24-hour) blood pressure (BP), metabolic and laboratory data were assessed. CV and all-cause mortality were evaluated over a mean follow-up of 16 years. Repetition of all measurements after 10 years allowed to evaluate also the risk of developing of office and out-of-office hypertension and echocardiographic left ventricular hypertrophy. Results: At baseline Tp-Te adjusted for confounders (c) showed a significant correlation with office, home and 24-hour BP but not with left ventricular mass. CTp-Te value predicted the risk of CV and all cause mortality both before and after adjustment for demographic and clinical variables, the increase being 31% and 13% for 1-standard deviation cTp-Te increase, respectively (P < 0.0001 and P < 0.002). This was the case also in hypertensives in which the corresponding increase in risk with 1-standard deviation increase of Tp-Te was 47% and 25% (P < 0.05 for both). CTp-Te did not predict the 10-year risk of developing office, home, ambulatory hypertension and left ventricular hypertrophy. Conclusions: Thus Tp-Te interval retains an independent prognostic value both in the general population and in its hypertensive fraction. This easily and cheaply obtainable variable may be employed for improving CV risk stratification, representing an useful measure to add to the recommended screening in hypertension.